Evaluation of different radiation levels on tomato stomatal density (Solanum lycopersicum L.) - Zárate-Martinez, William; Arellano-García, Marco Antonio; Ramírez-Godina, Francisca; Moreno-León, Karina; González-Sandoval, Dulce Concepción (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of this research was to evaluate the effect of different levels of photosynthetically active radiation (RFA) on the stomatal variables in the leaves of tomato plants. The treatments were as follows: T1 = 25%, T2 = 35%, T3 = 50%, T4 = 60% and T5 = 75% RFA blockade. Stomata density, stomatal index, stomatal length and width were calculated on the adaxial and abaxial surfaces in leaves 4 and 9. A higher stomatal density was found in the abaxial surface than in the adaxial surface, and in leaf 4 greater stomatal density than in leaf 9; in leaf 4 the stomata density range was from 105 to 219 stomata.mm-2 and from 86.9 to 132.9 stomata.mm-2 on the abaxial and adaxial surfaces respectively, however, the largest stomata were found in  leaves number 9. Radiation modifies tomato plants at the stomatal level.